Dermoscopic Features as Predictors of BRAF Mutational Status and Sentinel Lymph Node Positivity in Primary Cutaneous Melanoma - Filipović, Nika; Šitum, Mirna; Buljan, Marija (Dermatology Practical & Conceptual, 2021)
Dermoscopy is a diagnostic tool widely used in clinical practice for the detection of skin tumors, especially early stages of melanoma. Recent studies have shown that different dermoscopic features are associated with important prognostic parameters of melanoma, such as BRAF mutational status and sentinel lymph node status. More than half of all melanomas harbor a mutation in the BRAF oncogene. The current management of advanced-stage melanomas is greatly determined by the presence or absence of a mutation in this gene, as targeted therapy with BRAF kinase inhibitors is one of the first therapeutic choices for these patients. Sentinel lymph node status is one of the most significant predictors of a melanoma patient’s survival. Recent studies have shown that different dermoscopic patterns are also associated with sentinel lymph node status. This short article reviews studies that investigated correlations between dermoscopic features, BRAF mutation status and sentinel lymph node status.